The Digital Skill Improvement Program for Women of the HEPI Bandung Community Members in Using New Media - Moh Faidol Juddi; Agus Aprianti; Ratih Hasanah Sudrajat (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The tremendous number of internet usage in Indonesia does not only present positive impacts but also negative implications, particularly for women. Many of them experience difficulties related to digital security, not only for themselves but also for their children. Therefore, a digital literacy program targeting housewives, particularly members of the HEPI Bandung community, is critical. This program was conducted on 21 June 2023 by focusing on literacy to empower the participants to shop online wisely and control children in accessing digital media products effectively. This program has two stages. Number one is knowledge sharing aims at awareness improvements and a two-way sharing session to build knowledge and appropriate solutions. The program evaluation showed that literacy activities witnessed benefits for the participants to be wiser in using the internet. Hopefully, this program can be conducted sustainably in the future program.